2020
DOI: 10.21203/rs.3.rs-29286/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of complete renal response and mortality in early- and late-onset lupus nephritis: A multicenter retrospective study of a Japanese cohort

Abstract: Background: Most patients with systemic lupus erythematosus (SLE) progress to lupus nephritis (LN) within 5 years of their SLE diagnosis, although it is not uncommon for LN to develop at later time points. Here we evaluated the clinical features of early- and late-onset LN.Patients and Methods: We retrospectively analyzed the cases of 184 of the 201 patients who underwent a renal biopsy at Nagasaki University Hospital and associated community hospitals between 1990 and 2016 and were diagnosed as having LN. Ear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Nakano et al reported a lower relapse‐free rate in the delayed‐onset LN group, but no difference was observed between the 2 groups in terms of the maintenance medications used; 18 thus, this report may be informative. Ichinose et al previously reported that the early‐onset LN group was characterized by higher levels of anti‐dsDNA antibodies and hypocomplementemia with higher serological activity, and a lower index of chronicity compared to the late‐onset group 22 . Park et al reported that glomerular sclerosis in the chronicity index was an independent predictor of complete remission after start of therapy in LN patients 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nakano et al reported a lower relapse‐free rate in the delayed‐onset LN group, but no difference was observed between the 2 groups in terms of the maintenance medications used; 18 thus, this report may be informative. Ichinose et al previously reported that the early‐onset LN group was characterized by higher levels of anti‐dsDNA antibodies and hypocomplementemia with higher serological activity, and a lower index of chronicity compared to the late‐onset group 22 . Park et al reported that glomerular sclerosis in the chronicity index was an independent predictor of complete remission after start of therapy in LN patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, because a number of LN patients had not undergone histological diagnosis of LN, it was relevant to include these patients. Second, due to the retrospective nature of the study, heterogeneity in LN patients could not be fully excluded, which has been reported as a limitation with retrospective observational studies on LN 21,22,30 . Owing to the long study duration, the treatment regimen for LN varied based on time, and because many physicians treated patients in this study, treatment regimens were subtly different for each treating physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that earlier age of LN presentation associates with more severe disease manifestations and earlier mortality (15). However, a new Japanese study reported that early-onset LN has a better renal response and lower mortality rate during the first year of the diagnosis (16). The overall LN incidence was 60% after 5 years of post-SLE diagnosis (17).…”
Section: Epidemiologymentioning
confidence: 99%
“…The published treatment regimens of LN by the European League Against Rheumatism (EULAR)/European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) aimed for a full renal response during 12 months, although, more than 12 months of treatment might be required when the proteinuria presents before initiating the treatment (53). Despite the negative effects of age, sex, ethnicity, and histological findings, LN complete response to the immunosuppressive drugs was reported at 6 and/or 12 months, leading to better renal outcomes and less mortality rate (8,16). In general, in recent decades, while the prognosis of LN has improved due to the availability of advanced diagnostic and treatment facilities (6), there are still therapeutic challenges.…”
Section: Treatment Of Lnmentioning
confidence: 99%